Preventive Maintenance Scheduling with Age Replacement Method at CNG Station - Bangun, Cicilia; Jalil, Abdul; Amperajaya, Derajat; Rasjidin, Roesfiansjah (Aptisi Transactions On Technopreneurship (ATT), 2022)
CNG Mother Station focused to distribute Compressed Natural Gas for various industries. In the period from December 2020 to November 2021, there were 40 breakdowns in the distribution process machine causing delays in distribution of CNG. Company has to pay attention to the maintenance scheduling for vulnerabl components. This study aims to determine Preventive Maintenance scheduling and calculating maintenance costs using Age Replacement method for the critical components. The results showed that the critical components are Air Supply’s Hose (ASH) and Double Nipple Stage 4 (DNS-4). The proposed optimal replacement time interval for the ASH is 20 days where 19 component replacements are scheduled in 1 year with a cost reduction up to 4.8% compared to existing. The optimal replacement time interval for DNS-4 components is 24 days, which is scheduled for 16 component replacements in 1 year with cost reduction up to 29.1% compared to existing.